Effect of Probiotic Lactobacillus Casei on Secretory Immunoglobulin A (S-IgA) Levels in Rats Norvegicus Strain Wistar Post Ovariectomy - Safitri, Rani Safitri; Wijayanti, Tut Rayani Aksohini; Alim, Zainal (Sahabat Publikasi Kuu, 2025)
Estrogen causes the growth of lactobacillus colonies in the vagina which convert glycogen in superficial vaginal cells into lactic acid, resulting in a low vaginal pH which can inhibit the invasion of pathogenic bacteria. After menopause, lactobacillus growth is inhibited, vaginal secretions become thin, vaginal pH increases and the immune system becomes low. This study aims to determine the effect of Lactobacillus Casei extract on secretory immunoglobulin A levels and reduce vaginal acidity levels (pH) and increase the number of beneficial bacteria in the vaginal mucosa. The research design used was an experimental study with a post-test-only control group design using 24 female rats aged 8-10 weeks with a weight of 180-220 grams. Before treatment, the rats were ovariectomized, and the acclimation period was 14 days, then divided into 4 groups, namely: (K) without treatment, P1 received Lactobacillus Casei extract at a dose of 2ml / rat, P2 at a dose of 2.25ml / rat, and P3 at a dose of 2.5ml / rat. Lactobacillus Casei extract was given orally for 14 days. On the 15th day all rats were terminated. Vaginal acidity levels were measured using the swab method and IgA was measured using the ELISA method, while for bacterial identification tests, gram-positive staining was performed. The results of the one-way ANOVA test showed that Lactobacillus Casei extract can increase IgA levels and significantly reduce vaginal acidity levels by p = 0.003 and p = 0.000. The decrease in acidity levels is due to the deordelin bacillus which converts glycogen into lactic acid so that the vagina remains acidic, as well as the role of S-IgA on the surface of the vaginal mucosa which functions as an opsonin and APC (antigen-presenting Cell) to inhibit the growth of pathogenic bacteria in the vagina. This study concludes that the administration of Lactobacillus Casei extract can increase secretory Immunoglobulin A (S-IgA) levels and reduce vaginal acidity (pH) to normal.